Pathways mediating CRF-induced inhibition of gastric emptying in rats - (:unkn) unknown (My University, 1997)
The corticotrophin-releasing factor (CRF) is shown to be released during stress suggesting that CRF has a physiological role in the mediation of central nervous system (CNS) response to stress, including an inhibitory effect on gastric emptying. In the present study, we have examined the pathways by which intracerebroventricularly (icv) administered CRF and central CRF activation during stress alter the gastric emptying rate of saline (0.14 M), acid (50 mM), peptone (4.5%) and peptone after preload. The emptying rates of all these test meals were significantly (p < 0.05-0.001) delayed with increasing doses of icv CRF (0.001, 0.003. 0.01, 0.1, 0.3 and 1 nmol/10 μl), when compared with their icv saline-treated controls. The 1- nmol dose of CRF inhibited the emptying of acid, peptone and peptone after a preload by 43.8%, 64.1% and 81.1%, respectively. Twenty-minute swim stress delayed gastric emptying rate of saline, acid and peptone solutions significantly (p < 0.001) and the CRF receptor antagonist, α-helical CRF (8 nmol/10 μl, icv), applied before the swim stress, abolished the inhibitory effect of stress on the emptying rate of these solutions. Acute intragastric administration of capsaicin (2 mg/rat) and systemic capsaicin (125 trig kg- 1) treatment facilitated the gastric emptying rate of acid, peptone and peptone after preload significantly, almost abolishing the inhibitory effect of central CRF (p < 0.001). However, either capsaicin treatment had no effect on stress-induced inhibition of the gastric emptying of none of the solutions, except peptone after a preload. Our findings demonstrate that the gastric inhibitory response induced by swimming as a stress-producing stimulus is mediated by the endogenous release of CRF. They also suggest that CRF exerts its CNS actions on the gastrointestinal tract via vago-vagal, capsaicin-sensitive pathways, probably involving the central cholecystokinin (CCK) mechanisms.
Keywords: Acid; CCK; CRF; Gastric emptying; Peptone; Stress